Boosting interprofessional education through extension projects: coordination experience in a private higher education institution - Bertanda Soares, Lilian; Favoretti Galimberti, Geórgia; Mitre da Silva, Juliana; de Souza Mendonça, Paula Beatriz; Dutra Degli Esposti, Carolina (Guará Journal, 2025)
This paper reports the experience carried out at a private Higher Education Institution (HEI) through the coordination of an extension project aimed at undergraduate students from the fields of health and applied social sciences, grounded in the practice of Interprofessional Education (IPE). This is an experience report developed during two editions of the extension project “FAESA na Comunidade: Educação extramuros,” conducted between 2022 and 2023, with the participation of ten extension students in each edition from the Nursing, Dentistry, Psychology, and Journalism programs. The actions were planned in an interprofessional manner, based on an annual schedule that included monthly health education activities focused on disease prevention and health promotion. The interventions were carried out in companies, schools, and community settings, reaching approximately 3,100 people over the two years of the project. This report contributes to broadening the discussion on the importance of extension projects in professional health education, highlighting the need to promote such initiatives also within private HEIs, and underscores IPE as a formative strategy for training professionals capable of providing comprehensive care, in line with the principles and guidelines of Brazil’s Unified Health System (SUS) and the accreditation of university extension activities.
Keywords: Unified Health System; Professional training in health; Community extension; Interprofessional Education